It is strongly recommended to not conduct, fund, or publish research studies that use spot urine samples with estimating equations to assess individuals' sodium (salt) intake in association with health outcomes: a policy statement of the World Hypertension League, International Society of Hypertension and Resolve to Save Lives. - Campbell, Norm R.C.; Whelton, Paul K.; Orias, Marcelo; Cobb, Laura L.; Jones, Erika S.W.; Garg, Renu; Williams, Bryan; Khan, Nadia; Chia, Yook Chin *; Jafar, Tazeen H.; Ide, Nicole (Lippincott, Williams & Wilkins, 2023)
Spot urine samples with estimating equations have been used to assess individuals’ sodium (salt) intake in association with health outcomes. There is large random and systematic error in estimating sodium intake using this method and spurious health outcome associations. Substantial controversy has resulted from false claims the method is valid. Hence, the World Hypertension League, International Society of Hypertension and Resolve to Save Lives, supported by 21 other health organizations, have issued this policy statement that strongly recommends that research using spot urine samples with estimating equations to assess individuals’ sodium (salt) intake in association with health outcomes should not be conducted, funded or published. Literature reviews on the health impacts of reducing dietary sodium that include studies that have used spot and short duration timed urine samples with estimating equations need to explicitly acknowledge that the method is not recommended to be used and is associated with spurious health outcome associations.